2017
DOI: 10.1017/s0305741017000923
|View full text |Cite
|
Sign up to set email alerts
|

Neither Centre nor Local: Community-Driven Experimentalist Governance in China

Abstract: Based on findings from three years of site-intensive fieldwork at the local level, this article presents evidence to suggest that binary governance frameworks like centre-local relations are insufficient to understand certain local regulatory outcomes in contemporary China. I seek to specify a distinct type of local governance that has been emerging in recent years, which blurs existing binary concepts. It can be distinguished along two main dimensions: ostensible structure and modalities of governance. Two ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Public mistrust may exist at the grassroots level if local governments have restricted the activities of environmental NGOs, particularly when such NGOs are perceived to pose a threat to the interests of the local government. Informal communication arrangements between the government and non-state actorsincluding NGOs, 46 experts, and technocrats 47 are an alternative means whereby the public is involved in the policymaking process.…”
Section: China's Environmental Laws and Public Participationmentioning
confidence: 99%
“…Public mistrust may exist at the grassroots level if local governments have restricted the activities of environmental NGOs, particularly when such NGOs are perceived to pose a threat to the interests of the local government. Informal communication arrangements between the government and non-state actorsincluding NGOs, 46 experts, and technocrats 47 are an alternative means whereby the public is involved in the policymaking process.…”
Section: China's Environmental Laws and Public Participationmentioning
confidence: 99%
“…On the other hand, cities with a larger industrial base, hence a more energy-intensive economy, may consider the LCCP Program an opportunity to pursue other co-benefits such as economic restructuring, energy conservation, and local pollutant reduction. A case study by Shin (2017) found that industries and city governments formed an alliance to lobby for low-carbon piloting programs as a means to facilitate local pursuit of developing more energy-intensive green industries. Our key informant interviews, supplemented with review of policy documents, also suggested that many cities saw economic restructuring—upgrading the industrial base and transition toward a less energy-intensive and more services-oriented economy—as a co-benefit of joining in the LCCP Program.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…The choice between a centralized or a decentralized approach has long been the core of discussion in exploring an approach for better environmental performance. The supporters of a decentralized approach state that the local governments are closer to the people and environmental issues, thus they have better information and local knowledge which allows the better tailoring of policies to local conditions (Andersson & Ostrom, 2008;Kostka & Hobbs, 2012;Litvack et al, 1998;Oates, 1972;Shin, 2017;Sigman, 2014;Weibust, 2009). On the opposite side, the supporters of a centralized approach argue that enforcement tensions between the central level and the periphery are the result of decentralization, which causes local protectionism and pose major obstacles to the implementation of environmental policies (Beeson, 2010;Beyer, 2006;Gilley, 2012;Lo, 2015;Oates, 2008;Rooij et al, 2017).…”
Section: Introductionmentioning
confidence: 99%